KEDUDUKAN PENELITIAN KEMASYARAKATAN DALAM PERSIDANGAN PERKARA NARKOTIKA DENGAN TERDAKWA ANAK DALAM PUTUSAN NOMOR: 1/PID.SUS-ANAK/2024/PN.SKT - Damar Aji Kuncoroyakti; Muhammad Rustamaji (Verstek, 2026)
This research in legal writing aims to determine the position of social research in narcotics cases with child defendants and examine the judge's considerations in giving a criminal decision in decision number: 1/Pid.Sus-Anak/2024/Pn.Skt). who sentenced him to imprisonment for 6 (six) months at YPAN BHINA PUTERA Surakarta based on Article 127 paragraph 1 letter a of Law no. 35 of 2009 concerning Narcotics and Based on Article 183 and Article 184 of the Criminal Procedure Code. The type and nature of this research is normative legal research and is prescriptive in nature. The approach used is the case approach, the case approach is an approach carried out by examining cases that relate to legal issues and have received a decision by a judge that has permanent legal force. Legal materials are obtained from primary and secondary legal materials. The technique for collecting legal materials in this research is library research. The legal material obtained is then processed using the syllogism method which uses a deductive mindset. Based on this research, research results were obtained which showed that the position of the social research report in this case was in accordance with Article 60 of the Juvenile Criminal Justice System Law and based on Article 183 and Article 184 of the Criminal Procedure Code.